study the effect of overlap between the change in temperature and some chemical treatments in some fungi isolated from the seeds of barley Hordeum vulgare - Saadoon, Abdul amir Samir; marhoon, Khalil Abbas (Al-Qadisiyah Journal of Pure Science, 2017)
This study aimed to test the effect of temperature changesand the activity of sodium bicarbonate and asalcelik acid on vitality and activity of two fungi which are: Alternaria tenuissima and Fusarium oxysporum which isolated from barley (Hordeum vulgare) seeds. The results showed eristence asignificant difference in the effect of temperature and chemical substances on two isolated fungi growth at added of chemical substances to cultured medium at all tested concentration (5,10,15) mg/ ml to sodium bicarbonate and (250,500,750,1000) mg/ L asalcelik acid and also when the two isolated fungi grew at (10,20,30,40) cÂ° compared with control treatment and Albeltanol fungicide treatment. Also, the effect of sodium bicarbonate and asalcelik acid at same concentration were studied on planted rate of barley seeds, results showed increased relation ship between seeds plant and the riase of concentrations and this refer to that the chemical substances contain inhibtors for vital activity of associated fungi to seeds and these concentration lead to inhibitor of fungi growth at the same time it incourage barley growth and increased of its resistance. As to interference treatment , the results showed asignificant difference in the rates of seeds plant for various treatments on filter papers compared with control treatment while there is no asignificant difference compared with Albeltanol treatment in some treatments which are ranged (83.33% , 96.66%) of seeds plant ratio for various treatment at different temperature while the results of interference in radial growth of tested showed asignificant difference in fungi growth rate compared with control treatment but there is no asignificant difference in rates of fungi colonies diameters for some treatment compared with Albeltanol fungicide and this refer to the activity of these substances on vitality and activity of tested fungi.